Oral Abscess Caused by Chryseobacterium indologenes in Ball Python (Python regius); A Case Report - Tamai, Iradj Ashrafi (Antibiotics (Basel), 2021)
Chryseobacterium indologenes is an opportunistic pathogen isolated from human infections and, rarely, from some aquatic animals. A 3-year-old male ball python (Python regius) was admitted to the veterinary clinic by a pet owner because of acute respiratory and swallowing failure. During physical examinations, oral secretions and abscesses were observed in the mouth cavity and throat of the animal. After microbiological analysis including isolation, identification, and 16s rRNA sequencing, C. indologenes was detected as the main cause of the oral abscess in this case. Phylogenetic relatedness analysis showed a close relationship between this isolate and other strains isolated from human infections. Antimicrobial susceptibility testing revealed that the isolate was multi-drug resistant. However, it was very sensitive to minocycline, ceftazidime, and tetracycline. The patient was treated by antibiotic therapy and completely recovered after two weeks. To the best of our knowledge, this is the first incidence of C. indologenes in an oral abscess in a ball python. As a result we would consider this organism as an opportunistic animal pathogen with zoonotic potentiality.